Forming Quality and Fatigue Behavior of Self-Piercing Riveted Joints of DP590 and AA6061 Plates - Yinglian Jia; Zhichao Huang; Yongchao Zhang; Fan Zhang (Advances in Materials Science and Engineering)
Two kinds of self-piercing riveted (SPR) joints were prepared with DP590 and AA6061 plates. The forming qualities of the joints were studied using the finite element method. The relationships between the fatigue life and failure forms of the joints with different upper plates were discussed. Finally, the failure mechanisms of the joints were analyzed. The results show that the maximum static tension of DA32 joints (with an upper plate of DP590) is significantly greater than that of the other kind, and the fatigue life of DA32 joints is always longer than that of AA40 joints when with a 2.0 mm thick AA6061 aluminum alloy upper plate under the same fatigue load. The failure mode of SPR joints changes obviously due to different upper plates, and the fatigue life of the joints can be effectively improved by reducing the microvibration wear.